2016
DOI: 10.1051/0004-6361/201526533
|View full text |Cite
|
Sign up to set email alerts
|

SiO: Not the perfect outflow tracer

Abstract: Aims. Previous observations of the young massive star formation region IRAS 19410+2336 have revealed strong outflow activity with several interacting outflows. We aim to get a better understanding of the outflow activity in this region by observing the SiO and H 13 CO + emission with high angular resolution. SiO is known to trace shocked gas, which is often associated with young energetic outflows. With the H 13 CO + data, we intend to better understand the distribution of the quiescent gaseous component of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…5) Beuther et al (2003). The peak of the thermal SiO clump is shown by a square (measured in a beam size of 4") (Widmann et al 2016). This shows that the 12-GHz masers observed by Minier et al (2000), have an angular separation of ∼ 0.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…5) Beuther et al (2003). The peak of the thermal SiO clump is shown by a square (measured in a beam size of 4") (Widmann et al 2016). This shows that the 12-GHz masers observed by Minier et al (2000), have an angular separation of ∼ 0.…”
Section: Discussionmentioning
confidence: 58%
“…Figure 6 (right) shows the positions of other emission detected in this region.The thermal SiO (Widmann et al 2016) was observed with a 4-arcsec beam, larger than the total maser extent. Millimetre source mm1, position accuracy 0.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations